Tanggung Jawab Etis Guru Dalam Pembelajaran Pendidikan Agama Kristen Pada Masa Pandemi Covid-19 - Elisabet Juliana Steidy Gerungan; Max Ruindungan; Olivia C. Wuwung (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study is to analyze and describe ethical issues, the realization of the ethical responsibilities of teachers, the principal's efforts in managing the ethical responsibilities of teachers in learning Christian religious education during the Covid-19 pandemic. The researcher used a descriptive qualitative research method which was carried out at SMA Negeri 1 Manado. Data were collected through observation, interviews and documentation studies. From the results of data analysis and interpretation, it was found that: (1) Ethical problems in the implementation of Christian religious education learning during the Covid-19 pandemic at SMA Negeri 1 Manado found three important problems (2) The form of the teacher's ethical responsibility in learning Christian religious education is that the teacher has tried to realize his responsibilities wholeheartedly according to his conscience, also by realizing his calling to serve students and continuing to guide the spirituality of students in order to improve the quality of life and maturity of faith. (3) Efforts made by school principals in managing the ethical responsibilities of teachers have been carried out through evaluation meetings to confirm the rules regarding the main tasks and functions of professional teachers, problem solving, sharing and reflection meetings. From the results of data exposure, findings and discussion, it is certain that schools can help teachers provide free internet quotas as well as provide more learning media such as tabs or laptops to lend to underprivileged students, Christian religious education teachers can increase creativity in teaching also use learning media. Students should continue to improve their quality to become independent and have integrity.